Students' inquiry skills progression based on STEM approach and inquiry lab - Zahra Fathya Chaerunisa; Murni Ramli; Bowo Sugiharto (University of Muhammadiyah Malang, 2023)
Inquiry skills are one of the skills that students need to master in learning biological concepts. Inquiry skills are influenced by many factors, one of which is the lesson plan. This study aims to examine the effect of inquiry lab and STEM models on inquiry skills progression. The research design used was a quasi-experiment non-randomized control group, pretest-posttest design, with three treatments, namely discovery learning lesson plan as control (C), inquiry lab lesson plan (E1) and STEM lesson plan (E2) as treatment. The three classes were randomly selected from six classes XI of Science. All students in the selected class became the research sample (N = 98), with details. The control class consisted of 33 students, E1 32 students, and E2 33 students. The material taught in all classes is the human respiratory system. Data in inquiry skills progression is measured before and after treatment. The instrument takes the form of an essay test. Data analysis using ANCOVA (p = 0.05%). The results showed that the inquiry lab and STEM models had a significant effect, and the inquiry lab model had the best effect.